Tree by tree : saving North America's eastern forests - Meiners, Scott J., 1970- (Comstock Publishing Associates, an imprint of Cornell University Press, 2023)
"For decades, the forests of Eastern North America have faced pathogen and insect pests that have functionally removed tree species from the landscape. This book presents the ecological roles that the trees play, the biology of the threats faced, and the approaches that may remediate the problems"--